Choppers - David, Jack, 1968- (Minneapolis, MN : Bellwether Media, 2008)
Provides a brief history of customized motorcycles, describes the general features of choppers, and includes a glossary and resources.
Includes bibliographical references (p. 23) and index.
3.0
3-6
Keywords: Motorcycles -- Customizing -- Juvenile literature; Home-built motorcycles -- Juvenile literature; Motorcycles; Motorcycles